Monthly and seasonal variation in beach profile along the coast of Tiruchendur and Kanyakumari, Tamilnadu, India - Saravanan, S.; Chandrasekar, N. (Journal of Iberian Geology, 2010)
Beach profile survey has been carried out by the method described by Lafond and Prasada Rao (1954) and Emery (1961) between Tiruchendur and Kanyakumari beach, Tamilday, India. The average beach profile shapes in all stations are not identical. This is due to the large amount of sands that transported into the nearshore by longshore and cross-shore movement. In particular this difference is shown in the location of the high variability of heavy mineral distribution depicts the morphological changes. Record of monthly and seasonal beach profile obtained at the 10 beaches along the study area during the period between 2005 and 2006 yield an extensive dataset that could be used to determine the variations in the beach morphology and the processes responsible for the changes. Based on the beach profile measurements the changes were also critically examined and also the impact of intensive extraction of beach sand minerals along the beach profiles was investigated in order to know the morphological variation in the mining area.